Feasibility analysis of sentinel lymph node biopsy in breast cancer with axilla negative evaluation by physical examination but suspicious lymph nodes finding on preoperative imaging and metastasis confirmed with biopsy - CONG Binbin, CAO Xiaoshan, WANG Chuanjian, QIU Pengfei, SUN Xiao, CHEN Peng, LIU Yanbing, ZHAO Tong, ZHANG Zhaopeng, SHI Zhiqiang, BI Zhao, WANG Yongsheng (Zhongguo aizheng zazhi, 2023)
Background and purpose: With the increasing sensitivity of axillary imaging and ultrasound guided biopsy, some clinically axillary negative patients were upstaged to axillary positive (cN1) and received axillary lymph node dissection (ALND). This study aimed to assess the feasibility of sentinel lymph node (SLN) biopsy (SLNB) in patients with axilla negative evaluation by physical examination but suspicious lymph nodes finding on preoperative imaging and metastasis confirmed with a fine-needle aspiration cytology/core-needle biopsy pathology (FNAC/CNBP). Methods: This retrospective cohort study included patients with early breast cancer who had axilla negative evaluation by physical examination but suspicious lymph nodes finding on preoperative imaging and metastasis confirmed with a FNAC/CNBP from October 2015 to December 2022 in the Breast Cancer Centre of Shandong Cancer Hospital and Institute. All patients received ALND. The data were analyzed by using SPSS version 27.0 statistical software, and P<0.05 was considered statistically significant. Results: A total of 158 patients were identified to have axilla negative evaluation by physical examination but one to two suspicious lymph nodes finding on preoperative imaging and metastasis confirmed with FNAC/CNBP, 43.7% (69/158) of them had only one ALN metastasis after ALND, 15.2% (24/158) had only two ALNs metastases after ALND, and 41.1% (65/158) had more than two ALNs metastases after ALND. Among these cases, 65 patients received SLNB followed by ALND, and the false negative rate of SLNB was 0%. Positive non-SLN metastasis rate was 0 in the 61.5% (40/65) patients with 1-2 positive SLNs metastasis. One, two, three and more than three non-SLN metastasis rates were 10.8% (7/65), 4.6% (3/65), 6.2% (4/65) and 16.9% (11/65), respectively (P=0.042). Conclusion: SLNB was safe and feasible in patients with axilla negative evaluation by physical examination but one to two suspicious lymph nodes finding on preoperative imaging and metastasis confirmed with a FNAC/CNBP. In these patients, the axillary lymph node tumor burden was high, and exhaustive radiotherapy and systematic treatment were needed to control reginal disease.